(untitled) - Goodman, A. W. (New York, 1963)
The content of a course in analytic geometry and the calculus, is reasonably standard, and a glance at the table of contents of this book will show that all of the essentials have been included, and these items do not require any further discussion.
Keywords: Hình học giải tích,Geometry, analytic